2006
DOI: 10.4315/0362-028x-69.6.1354
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Evolution during Storage of Seasoned Olives Prepared with Organic Acids with Potassium Sorbate, Sodium Benzoate, and Ozone Used as Preservatives

Abstract: The effect of potassium sorbate, sodium benzoate, and ozone in combination with citric, lactic, and acetic acids on the microbial population of seasoned table olives of the olive 'Aloreña' cultivar was studied in both fresh (FF) and stored fruits (SF). The inactivation/growth curves were modeled and the biological parameters estimated, with yeast used as the target microorganism. Regardless of the acid added, potassium sorbate showed a general inactivation effect on yeasts in the products prepared from both FF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 30 publications
1
9
1
Order By: Relevance
“…L* values fluctuated during storage, no difference was found between the beginning and end of storage. In contrast to research findings, Arroyo Lopez et al (2006) and Sanchez-Gomez et al (2013) reported that L* values decreased during storage (Table 5).…”
Section: Instrumental Color and Hardness Changes During Storagecontrasting
confidence: 66%
See 1 more Smart Citation
“…L* values fluctuated during storage, no difference was found between the beginning and end of storage. In contrast to research findings, Arroyo Lopez et al (2006) and Sanchez-Gomez et al (2013) reported that L* values decreased during storage (Table 5).…”
Section: Instrumental Color and Hardness Changes During Storagecontrasting
confidence: 66%
“…Therefore, the green color should be preserved as much as possible during storage (Arroyo- Lopez et al, 2006).…”
Section: Instrumental Color and Hardness Changes During Storagementioning
confidence: 99%
“…Previous works have demonstrated the effectiveness of potassium sorbate to control fungi growth [29]. The yeast inhibition, together with the low salt concentration in the packed product (<6%), favoured the growth of LAB [30,31]. LAB populations' survival and growth during the storage of diverse green table olives is well documented [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Before packing and marketing, olive producers add to the brine some weak acids (lactic, acetic, citric, sorbic, and benzoic acids) to prevent yeast growth and achieve a “sufficient level of sanitary risk” (Warth 1977; Liewen and Marth 1985; Luck 1990; Arroyo‐Lopez and others 2006); this practice is permitted in table olives in many countries and the effect of these preservatives on yeast microflora and pathogens is known and documented (Marsilio and Chichelli 1992; Garrido‐Fernandez and others 1997; Turantas and others 1999; Nakai and Siebert 2004; Arroyo‐Lopez and others 2008) Moreover, some authors suggest to add to brine little amounts of ascorbic acid, as it could prevent color change within the storage time (Arroyo‐Lopez and others 2006).…”
Section: Discussionmentioning
confidence: 99%